δ-Keto Aminoacrylonitriles and δ-Keto Aminoenones from 1-Pyrrolines, Cyanoacetylenes, and Acetylenic Ketones - Oparina, Ludmila A.; Mal’kina, Anastasiya G.; Kolyvanov, Nikita A.; Ushakov, Igor A.; Saliy, Ivan V.; Apartsin, Konstantin A.; Trofimov, Boris A. (Synthesis, 2022)
The ring-opening/functionalization of 1-pyrrolines by cyanoacetylenes or acetylenic ketones (20–80 °C, MeCN, H2O) affords δ-keto aminoacrylonitriles and δ-keto aminoenones, mostly as the Z-isomers, in up to 85% yields. The synthesis involves C(2)–N bond cleavage in the intermediate hemiaminal resulting from the intermediate 1,3(4)-dipolar 1-pyrroline/acetylene complexes and water.
Keywords: cleavage reactions; electrophilic acetylenes; multicomponent reactions; 1-pyrrolines; zwitterions